2001
DOI: 10.1002/chp.1340210205
|View full text |Cite
|
Sign up to set email alerts
|

Value of unstructured time (breaks) during formal continuing medical education events

Abstract: The results suggest that unstructured time (breaks) should be included in formal CME events to help physician learners integrate new material, solve individual practice problems, and make new meaning out of their experience. The interaction between colleagues that occurs as a result of the provision of breaks is perceived as crucial in aiding the process of applying knowledge to practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…One study demonstrated that interacting with colleagues, even during "break times," contributes to learning and is perceived as very satisfying. 18 These findings suggest that the content of faculty development programs may not be the important factor in increasing teacher identity; many different kinds of programs might yield similar responses.…”
Section: Differences Between Subgroupsmentioning
confidence: 99%
“…One study demonstrated that interacting with colleagues, even during "break times," contributes to learning and is perceived as very satisfying. 18 These findings suggest that the content of faculty development programs may not be the important factor in increasing teacher identity; many different kinds of programs might yield similar responses.…”
Section: Differences Between Subgroupsmentioning
confidence: 99%
“…Much informal learning occurs also in the discussions that occur over coffee or in small groups. 2 Lastly, the hidden curriculum messages might be seen in the program plan, where the time allocated or program placement may transmit a message about the value placed on particular content.…”
Section: Introductionmentioning
confidence: 99%
“…1 However, nearly half of the participants in this study 118 chose informal peer consultants solely on the basis of their expertise, suggesting an evolution in family physicians' selection criteria from those used by physicians in the 1978 to 1992 studies analyzed by Verhoeven et al 1 The present study was limited to the analysis of participants' criteria for selecting informal peer consultants, the frequency of their requests for information from peers, and their approach toward evaluating the information peers provided. Future studies might provide more detailed analyses of the functions of informal consultations at various stages of physicians' learning, similar to the Tipping et al 18 analysis of the functions of informal peer communications during unstructured time at formal CE events. Replication research should also address the limitations of this study's recruitment strategy and sample size.…”
Section: Discussion Of Findings and Possible Strategies To Enhance Rementioning
confidence: 94%